Innovative Work Behavior on Education Sector: A Systematic Literature Review - Aziz, Benni; Wardi, Yunia; Rino, Rino (Green Publisher Indonesia, 2025)
The need for innovation in the learning process, education management, and adaptation to digitalization highlights the importance of understanding the factors that influence innovative work behavior among teachers, lecturers, and educational staff. This study follows the PRISMA protocol through the stages of identification, screening, feasibility assessment, and final selection. Articles were collected from the Scopus, Web of Science, Google Scholar, SINTA, and DOAJ databases using structured keywords and inclusion criteria that included empirical research, a focus on IWB in the context of education, full-text availability, and publication between 2018 and 2024. Of the 427 initial articles, only 42 studies met the final criteria and were analyzed thematically. The results of the study show a significant increase in IWB research in the education sector with a predominance of quantitative approaches, particularly SEM-PLS. The main factors that play a role as antecedents of innovative work behavior include transformational leadership, psychological empowerment, knowledge sharing, work engagement, and creative self-efficacy. Various mediating variables such as knowledge sharing, work engagement, thriving, and creative self-efficacy were also found to be consistent, while moderating variables have rarely been studied. In addition, IWB has been proven to contribute positively to teacher performance, learning innovation, and organizational effectiveness. This study concludes that although research on innovative work behavior shows positive developments, it is necessary to expand the context, methodological diversity, and integration of digital variables and the climate of innovation in future research.